Smart nanotechnology with applications - Bhargava, Cherry, 1982-; Sachdeva, Amit; Sharma, Pradeep Kumar, 1957- (Boca Raton : CRC Press, 2020)
This comprehensive reference text discusses advance concepts and applications in the field of nanotechnology. The text presents a detailed discussion of key important concepts including nanomaterials and nanodevices, nano-bio interface, nanoscale memories, and semiconductor nanotechnology. It discusses applications of nanotechnology in the fields of aerospace engineering, cosmetic industry, pharmaceutical science, food industry, and the textile industry. The text will be useful for senior undergraduate and graduate students in the field of electrical engineering, electronics engineering, nanotechnology, and pharmaceutical science. Discussing fundamental, advanced concepts and their applications in a single volume, this text will be useful as a reference text for senior undergraduate and graduate students in the field of electrical engineering, electronics engineering, nanotechnology, and pharmaceutical science. It comprehensively discusses important concepts such as nano-robotics, carbon-based nanomaterials, and nanoscale memories. The text discusses advanced concepts of nanotechnology and its applications in the fields of textile, pharmaceutical sciences, aerospace, and food industry. It will be an ideal reference text for senior undergraduate and graduate students in the field of electrical engineering, electronics engineering, nanotechnology, and nanoscience.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Electronics / General; TECHNOLOGY / Nanotechnology; Smart materials; Nanotechnology